Inhibition of Matrix Metalloproteinase-7 Attenuates Subpleural Fibrosis in Rheumatoid Arthritis-Associated Interstitial Lung Disease - Li Xiong; Li-Mei Liang; Shu-Yi Ye; Xiao-Lin Cui; Shi-He Hu; Chen-Yue Lian; Wen-Jia Sun; Yang-Ping Lv; He-De Zhang; Meng Wang; Fei Xiang; Liang Xiong; et al. (Biomedicines)
Background: Rheumatoid arthritis-related interstitial lung disease (RA-ILD) is a significant complication of RA which lacks effective treatments with high mortality. This study aimed to investigate the role of matrix metalloproteinase-7 (MMP-7) in mediating RA-ILD. Methods: Based on the database of RA-ILD patients, a bioinformatics analysis was performed. A protein–protein interaction (PPI) network focusing on MMP-7 was simulated. Pleural mesothelial cells (PMCs) were treated with RA-ILD patients’ serum or RA-ILD-related inflammatory factors, and the protein expressions of collagen-I and MMP-7 were examined. An arthritis model was established using complete Freund’s adjuvant (CFA). Changes in the weight and joints of mice were recorded, and lung tissues were evaluated by Masson staining and Sirius red stain techniques. MMP-7 inhibitor, MMP-7 siRNA and MMP shRNA lentivirus were used to inhibit MMP-7 and investigate changes in collagen-I and fibrosis in vivo and in vitro. Results: MMP-7 was found to be significantly expressed in RA-ILD lung tissue by bioinformatics analysis, and MMP-7 to maybe interact with collagen-I. In vitro experiments indicated cytokines IL-1β, IL-6 and TNF-α promoted MMP-7 and collagen-I expression in PMCs. Serum obtained from patients with RA-ILD also upregulated MMP-7 and collagen-I expression in PMCs. Inhibition of MMP-7 with MMP-7 siRNA or MMP inhibitor prevented collagen-I synthesis in PMCs. In vivo, CFA induced arthritis and subpleural lung inflammation in rats, but the MMP-7 inhibitor and MMP-7 siRNA attenuated CFA-induced lung inflammation and subpleural lung fibrosis. Conclusions: MMP-7 mediated subpleural lung inflammation as well as fibrosis in RA-ILD. It provided theoretical and experimental support for MMP-7 being a therapeutic target in RA-ILD.